(untitled) (Journal of Health, Technology and Science (JHTS), 2025)
This study aims to analyze the role of pharmacists in providing education on the use of herbal medicines together with prescription drugs. Herbal medicines are often used by the public as part of alternative medicine, but their use together with prescription drugs can pose a risk of dangerous interactions if not known by patients or health workers. Pharmacists have an important role in providing information and education to patients regarding the benefits and risks of using herbal medicines. Based on the results of the study, it was found that patient understanding of the risks of interactions between herbal medicines and prescription drugs is still low. This shows the need for an active role of pharmacists in providing education and ensuring the safety of drug use for patients. Education provided by pharmacists includes potential side effects, drug interaction mechanisms, and proper use to prevent negative impacts. With the knowledge and expertise they have, pharmacists can help patients make wiser decisions about the use of herbal medicines. This study recommends that pharmacists be more proactive in communicating with patients, providing clear information, and increasing public awareness of the importance of safe and rational drug use. Thus, pharmacists become one of the spearheads in ensuring the use of herbal and prescription medicines synergistically without sacrificing patient safety aspects.